Systematic Review of Art Therapy in Children with Autism Spectrum Disroder (ASD) - Nanda Audia Vrisaba; Ananta Yudiharso (Universitas Muhammadiyah Jember, 2021)
Autism Spectrum Disorder (ASD) children tend to be isolated from their environment because their limitation in communication. Many therapies can be applied to ASD children, one of them is art therapy. Art can be used as a medium of communication for the children. In art, children do not feel they are under therapy thus minimizing their resistance level. Art encourages the children to tell stories clearly rather than asking them to tell orally or verbally. This article explores several systematic analysis methods of art therapy applied to ASD children durimg 2004 to 2019. This articles reviewes 15 journal, including objectives, treatment procedures, and results. The review shows that art therapy has effective impact on the development of ASD children. Most research results show the increase in communication skills that enable the children to easily expressing their feelings and their involvement in social interactions.